Regeneration of the digestive tube with stem cells stimulated by infrared light: Regeneración del tubo digestivo con células madre estimuladas por luz infrarroja - de Taboada, María Teresa (2018)
Intestinal Barrier and Intestinal Permeability The "Intestinal Barrier" (BI) covers an area of approximately 400 m2 and requires about 40% of theenergy expenditure of the body. Among its functions are to avoid the loss of water and electrolytes and the entry of antigens and microorganisms to the human organism1. At the same time, the BI must allow the exchange of molecules between the body and the environment, as well as the absorption of nutrients from food consumed. The specialized adaptations of the intestinal mucosa of the mammal perform two functions apparently opposite: first, allow a peaceful coexistence with the intestinal microbiota without cause chronic inflammation and, secondly, provide a defensive inflammatory and response measure according to the threat of pathogens    DOI 10.25176/RFMH.v18.n4.1725